Determination of Business Opportunities and Implications for the Level of Community Welfare - Marta Widian Sari; M. Havidz Aima; Elfiswandi Elfiswandi (International Journal of Social Science and Business, 2023)
Great business opportunity can be utilized by the community and the government in increasing state income and improving the welfare of the community, especially the tourism business. This study aims to analyze the effect of family support and activities on business opportunities and the level of community welfare and tourism. The method used is descriptive. This research was involving the marine tourism community as subject. The study used primary data (questionnaires) from 209 respondents from the tourism community. The method used is Structural Equation Modeling Analysis with Partial Least Square (PLS). This study shows family support, tourism activities, business opportunities, and welfare levels as valid and reliable constructs lowest loading factor 0.6 and Cronbach alpha more than 0.7. The findings of this study indicate that partially family support and activity have a significant effect on community business opportunities. Further findings reveal that the level of welfare is significantly influenced by tourism activities, but not significantly influenced by family support. Regarding the mediating variable, business opportunities significantly mediate family support on welfare levels but do not significantly mediate activities and some results. This study is contradictory with previous theories and research, because of the different phenomena and objects studied.